Effect of carbon-based nanomaterial on growth of microalgae and production of exopolysaccharides - Fakhirruddin, Fakhriah; Azmi, Azlin Suhaida (2017)
Microalgae are a source of numerous compounds that can be used in different industries. Significantly, microalgae can produce exopolysaccharides (EPS) and the synthesis of EPS can be amplified under several stress conditions. Carbon- based nanomaterials have attracted great deal of interests by researcher due to many unique properties (i.e. chemical, physical and thermal properties). Thus, the exposure to various C-based nanomaterials could induce microalgal cell stress and affect synthesis of EPS. In this review, the potential two C-based nanomaterial, carbon nanotubes (CNT) and graphene in affecting growth of microalgae and microalgal EPS production are discussed. Majorly, CNT and graphene inhibit growth rate of different species of microalgae and affect compositions and amount of microalgal EPS produced. The effect of CNT and graphene was observed on several species such as Chlorella vulgaris, Chlamydomonas reinhardtii, Dunaliella tertiolecta and Raphidocelis subcapitata.